IN-VITRO IN-VIVO AND EFFICACY OF AGROCHEMICALS, BIOLOGICAL DERIVED FORMULATIONS AND BIOAGENTS AGAINST SHEATH BLIGHT OF RICE (Journal of Plant Disease Sciences, 2026)
Rhizoctonia solani Thanatephorus cucumeris in vitro Trichoderma viride in vivo Trichoderma virideKuhn (Teleomorph: (Frank) Donk) is a soil-borne, necrotrophic fungus belonging to the division Basidiomycota Sheath blight is one of the most important and widespread diseases affecting rice in all major rice-growing regions of the world and causes significant reductions in grain yield. In India, rice sheath blight has been reported to cause yield losses of up to 54.3%. Sheath blight management was evaluated through in vitro and in vivo studies using agrochemicals, biologically derived formulations and bioagents. Under conditions, Propiconazole 25% EC (T ) exhibited the highest mycelial growth inhibition (92.95–96.82%), whereas Pyrazosulfuron ethyl 10% WP (T ) was the least effective. Among biologically derived formulations, Beejamrit (T ) showed the highest efficacy, while Agniastra recorded the lowest growth inhibition. In bioagent evaluation, (T ) showed maximum growth inhibition (36.61%), whereas PSF 173 was least effective. Under conditions, Propiconazole 25% EC (T ) resulted in the minimum disease incidence (12.11%), while Pyrazosulfuron ethyl 10% WP showed the highest incidence. Among biologically derived formulations, Beejamrit (T ) recorded the lowest disease incidence (16.62%), whereas Agniastra (T ) showed the highest (26.24%). In bioagent treatments, (T ) effectively reduced disease incidence (18.68%), while PSF 173 (T ) recorded the maximum incidence (22.98%). These results highlight the comparative efficacy of chemical and biological approaches for managing sheath blight disease of rice.
Keywords: Agrochemicals; Bioagents; Biologically derived formulations; Rice; Sheath blight